Additional remarks on Deltanthura palpus (Isopoda: Anthuroidea: Paranthuridae), with an amended diagnosis for Deltanthura and a note on the ontogeny of pereopod 7 - Shiraki, Shoki; Shimomura, Michitaka; Kimura, Taeko; Kakui, Keiichi (Zootaxa, 2026)
Deltanthura Shiraki, Shimomura & Kakui, 2022 is a monotypic paranthurid genus established for Deltanthura palpus Shiraki, Shimomura & Kakui, 2022, which was described from a single female lacking oostegites. It was concluded from the original description that D. palpus is neotenous, because the specimen lacked pereopod 7. Recently collected material revealed that the specimen originally described was a manca-stage individual, and that the condition of pereopod 7 differed among the ontogenetic stages: it is absent in smaller specimens (6.84–10.92 mm; mancae); it has only a few setae and a tiny unguis in middle-sized specimens (12.87–13.67 mm; smaller female-like specimens and a subadult male); and it is generally similar in shape to a pereopod 6 with many setae and a normal-sized unguis, but shorter and narrower (less than 0.7 times pereopod-6 length) in larger specimens (16.56–21.14 mm; a larger female-like specimen and adult males). We present an amended diagnosis for the genus and the amended key to the genera in Paranthuridae, suggest that primary males may be present in D. palpus, and briefly discuss the possibility that this species may be undergoing an evolutionary process toward the loss of pereopod 7 (true neoteny).